2017
DOI: 10.1002/adsu.201700096
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Doping Facilitates Water Dissociation in Magnesium Oxide

Abstract: is the most ubiquitously used form of energy, including in electricity generation, power plants, or industry. [5] In this context, in 2011, the International Energy Agency estimated in a report entitled "Solutions for a low-carbon energy future" that global energy loss through waste heat accounts for two-third of the overall energy production. [6] Therefore, methods suitable for reduction of waste heat or reutilization thereof could contribute significantly to a sustainable energy management. [7][8][9] Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In general, raw materials have drawbacks, such as a low cycle stability [11], a low conversion rate [12], a high sintering effect [13], and a high cost. To overcome these drawbacks, either doped TCES materials or mixture of a TCES material with other suitable inert or TCES materials have been created [14][15][16][17][18]. For instance, the cycling stability of doped-CaCO 3 with SiO 2 was improved as reported by Chen et al [14], and doping MgO by 10% CaO has enhanced the hydration rate of MgO [15].…”
Section: Introductionmentioning
confidence: 99%
“…In general, raw materials have drawbacks, such as a low cycle stability [11], a low conversion rate [12], a high sintering effect [13], and a high cost. To overcome these drawbacks, either doped TCES materials or mixture of a TCES material with other suitable inert or TCES materials have been created [14][15][16][17][18]. For instance, the cycling stability of doped-CaCO 3 with SiO 2 was improved as reported by Chen et al [14], and doping MgO by 10% CaO has enhanced the hydration rate of MgO [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the screening of TCES materials has focused only on raw or doped materials. Overall, raw TCES materials possess drawbacks, such as sintering [21,22,23], slow conversion rates [22], low cycling stability [17], low thermal conductivity [17], and high costs [17,24], and researchers have attempted to overcome these drawbacks by doping or mixing raw TCES materials with other TCES/sensible heat storage materials [24,25,26,27,28]. For instance, the cycling stability of a calcium oxide (CaO)/CaCO 3 system decreased with the number of cycles because the carbonation of CaO to form CaCO 3 was significantly slow and sintering of material occurred at high temperatures [29].…”
Section: Introductionmentioning
confidence: 99%
“…Junichi et al developed a 6.8 wt.% LiCl/Mg(OH) 2 system that drops the dehydration temperature of magnesium hydroxide, from 277 °C to 233 °C, being able to store 816 MJ/m 3 volumetric heat storage capacity [ 19 ]. Muller et al found that calcium doping of magnesium oxide results in significantly increased water dissociation rates, thus enhancing both hydration rate and reaction completeness of hydration compared to pure MgO [ 20 ]. Zamengo et al prepared a Mg(OH) 2 /MgO system supported on expanded graphite.…”
Section: Introductionmentioning
confidence: 99%